Ｒesearch on Hydroforming for Automobile Front Sub-frame - LIU Xiao-jing; YANG Ｒan; FENG Zhang-chao; WANG Zhe (Journal of Harbin University of Science and Technology)
Winkles，ruptures and excessive thinning are the forming defects for curved hollow components． Taking a car front sub-frame as the research object，the hydroforming of sub-frame was studied by combing numerical simulation and forming experiment． The effect of bending parameters on the thinning during the bending process was studied． The influences of main process parameters on the forming quality were considered，such as the internal hydraulic pressure，the axial feeding and the loading path． Experiments of bending，preforming and hydroforming were carried out based on the optimum parameter of the simulation． The thickness distribution of typical section was measured and compared with the simulation result． It shows that the lateral of corner easily appears fracture and excessive thinning，and these forming defects could be avoided through optimizing the bending process parameters． The numerical simulation results have good conformity to experimental ones in the wall thickness distributions，their overall tendency of thickness distributions tend to be consistent in typical section，and the maximum difference of thickness between simulation and experiment results is 6%，which indicates that the proposed optimization method is feasible and can provide an effective guidance for the hydroforming of subframe．